From post‐political to authoritarian planning in England, a crisis of legitimacy. Issue 2 (27th October 2021) - Fearn, Gareth; Davoudi, Simin
Abstract: This paper argues that the crisis of post‐politics has sparked an authoritarian turn in spatial planning in England. The proposed reform of the English planning system in 2020 is a defining moment, marking not only the failure of consensus‐seeking politics in governing dissents but also the rising authoritarian responses to fix it. This is manifest in the intensification of state control, strengthening of executive power, and decline of democratic institutions, with a shift of emphasis from techno‐managerial to executive‐punitive practices, and from seemingly consensual to openly antagonistic approaches. This drift to authoritarianism has been justified by invoking a "state of exception, " whereby the established rules and procedures are displaced by the appeal to "exceptional" circumstances, such as emergencies, national securities, and global pandemics. We draw on a case study of shale gas "fracking" in England to show how authoritarianism has crept into planning processes through changes in legislation, reconfiguration of rules, rescaling of decision‐making, and shrinking of democratic spaces. We discuss the role of a "political moment" in the politicisation of fracking, arguing that the return of the political has engendered antagonistic and exclusionary practices, rather than the agonistic pluralism that planning scholars have called for. In managing planning conflicts, consent, compromise, and co‐option are increasingly complemented or replaced by discipline, control, and explicit exclusion. Instead of denying, neutralising, or suppressing antagonism by calling for consensus, authoritarian politics exaggerates it by establishing frontiers between legitimate and non‐legitimate voices of dissents. The paper concludes by emphasising that the authoritarian turn can only offer a contingent and fleeting solution to the failure of post‐political planning to deliver neoliberal pro‐growth goals. It cannot eradicate the crisis of legitimacy in planning, nor can it foreclose the political struggle for fixing its meaning and purpose. Abstract : This paper argues that the crisis of post‐politics has sparked an authoritarian turn in spatial planning in England, and that the proposed reform of the English planning system in 2020 is a defining moment that marks the failure of consensus‐seeking politics in governing dissents and the rising authoritarian responses to fix it. We draw on a case study of shale gas "fracking" in England to show how authoritarianism has crept into planning processes through changes in legislation, reconfiguration of rules, rescaling of decision making, and shrinking of democratic spaces.